PORTRAIT PHOTO STUDY AS COMMUNICATION MEDIA IN A POLITICAL CAMPAIGN - I Putu Dudyk Arya Putra; Ramanda Dimas Surya Dinata; Agung Wijaya (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2019)
Campaign in principle is a process of individual or group communication activities institutionalized and aims to create a certain impact. Political contestation at this time currently uses various media as mass communication. One of the most widely used media communications in political campaigns is portrait photos. In a portrait photo that is seen is the protrusion of a figure in a picture frame. Portrait photos are widely used in today's political campaign media and appear to be a mandatory element in campaign media. Its almost certain when there are political activities such as general elections, presidential elections and others, campaign media that display portraits of political figures can be found in strategic public places. Usually photos that are selected or set to be communicative and the appearance of the expressions from political figures sparks smiles and laughter to gain sympathy from their constituents. The form of portrait photos in campaign media appears in various mediums such as banners, billboards, pins, stickers, posters, t-shirts, and others. The communication that is built in the portrait photo media is non verbal communication that requires viewers to see visuals or images. This become interesting to study because portrait photos are not enough to only be read as visual that display personal figures but can be seen from a social angle because their presence functions as signs and illustrative elements.